Digital Literacy Landscape of Novice Voters in the 2024 Election in Indonesia - Abisono, Firya Qurratu'ain; Hastjarjo, Sri; Destyani, Vincentia Ardhana (Universitas Negeri Yogyakarta, 2024)
Elections are one of the times when Indonesian democracy runs because the people themselves will choose a pair of president and vice president candidates along with the existing legislature. Voters need to have enough information about the candidates in order to choose the best among them, especially novice voters. Novice voters need to have good digital literacy in facing the upcoming 2024 elections. The 2024 election itself is mostly from young people who are novice voters. The purpose of this study is to determine the digital literacy readiness of novice voters in 2024 elections. In addition, it will also be known what factors influence this readiness and the impact of the readiness of novice voters on their participation in the election later. This study uses a quantitative approach with descriptive methods. Data collection was carried out using questionnaires as primary data and literature studies as secondary data. The results and conclusions obtained in this study are that the majority of novice voters use social media as an information platform about the 2024 elections with varying levels of trust in the information. Most of the respondents chose not to share the information obtained related to the verification of uncertain news.